Criterios para la valoración hidrogeomorfológica de cursos fluviales. Aplicación en Aragón - Ballarín Ferrer, Daniel; Mora Mur, Daniel; Diaz Bea, Elena; Echevarría Arnedo, María Teresa; lbisate González de Matauco, Askoa; Montorio Llovería, Raquel; Ollero Ojeda, Alfredo; Sánchez Fabre, Miguel (Geographicalia, 2016)
A new assessment system based on hydrogeomorphological parameters to determinate the ecological status of rivers in Aragon has been designed. Different indicators have been used: naturalness, continuity and complexity of the basin, discharge, channel and riparian corridor. The fluvial network has been divided in 723 fluvial reaches, functionally homogeneous, which have been evaluated. The results obtained are the following: 1.156'34 km (17,7% of total length) in very good ecological status; 1.697,92 km (26%) in good status;1.510,12 km (23,1%) in acceptable status; 1.221,14 km (18,7%) in non acceptable status and, finally, 939,27 km (14,4%) of the fluvial network are very modified.